THE INFLUENCE OF TOURIST PREFERENCE ON THE DECISION TO VISIT WITH TOURISM ATTRACTION AS MEDIATION (STUDY ON TOURISM OBJECT OF ORANGE TERNATE FORT) - Adhit Yoga Pratama; Ida Hidayanti; Sulfi Abdul Haji (UIN Raden Mas Said Surakarta, 2023)
This study aims to determine the effect of tourist preferences on visiting decisions through tourist attractions. This research is a quantitative research. The population in this study is all visitors to Beneteng Oranje, Ternate city. The number of research samples is 110 respondents. The data analysis technique used in this research is path modeling analysis using Smart Partial Least Square (PLS) version 4 as a statistical test tool. The results of this study indicate that: (1) Tourist preferences have a significant effect on visiting decisions; (2) Tourist preferences have a significant effect on tourist attractiveness; (3) tourist attraction has a significant effect on visiting decisions; (4) Tourist preferences have a significant effect on visiting decisions through tourist attractions . Keywords: Tourist Preferences, Tourist Attractiveness and Visiting Decisions.